(untitled) - Farmer, Jacqueline; Tildes, Phyllis Limbacher (Watertown, MA, 2004)
Presents a history of pumpkins, how they are grown, their nutritional value, and recipes using pumpkin.
Keywords: Pumpkin; Juvenile literature